Anti-PD-L1 DNA aptamer antagonizes the interaction of PD-1/PD-L1 with antitumor effect. Issue 3 (15th December 2020) - Gao, Tian; Mao, Zheng; Li, Wenjing; Pei, Renjun
Abstract : A DNA aptamer targeting PD-L1 antagonizes the interaction of PD-1 and PD-L1 with antitumor effect. Abstract : Tumor immune evasion enables cancer cells to escape destruction by the immune system, which causes poor prognosis and overall survival of some tumor patients. The binding of PD-L1 on tumor cells to PD-1 on T cells suppresses T cell function, and the axis is considered one of the major pathways mediating tumor cells to evade immune surveillance. The PD-L1 ligation of T cells has a profound inhibitory effect on the growth, cytokine secretion, and development of cytotoxicity. Aptamers, known as chemical antibodies, are single-stranded oligonucleotides with high affinity. In this work, we take a cell-SELEX with the engineered PD-L1-expressing cells as a target to obtain the aptamer, designated PL1, which specifically binds to PD-L1 with a K d value of 95.73 nM, resulting in the inhibition of PD-1/PD-L1. The aptamer PL1 could restore the proliferation and IFN-γ rescue from the T cell inhibited by the PD-1/PD-L1 axis, and inhibit the growth of the CT26 colon carcinoma. The similar tumor inhibition efficacy and binding capacity of the aptamer PL1 as an antibody indicate that the aptamer PL1 can serve as an alternative therapeutic agent for cancer immunotherapy since the use of antibodies is often restricted by high cost, large size and poor tumor penetration.